The current management of Glaucoma - Avilés-Calderón, Gustavo (2023)
Glaucoma is an eye disease characterized by loss of vision as a result of damage to the optic nerve and is closely related to increased intraocular pressure, although causes of vascular and genetic origin are also being considered. The greatest importance of this disease is that it is usually asymptomatic, and in its natural evolution it leads to irreversible blindness, therefore its early diagnosis and early treatment will be of the utmost importance to stop the disease or failing that, slow down the rate of progression with the ultimate goal of reducing the significant visual sequelae that this disease can leave, leading to visual impairment, blailnes and social dependence of the patient. The only modifiable risk factor is intraocular pressure, which is why all medical, laser and surgical treatments are aimed at lowering intraocular pressure. The objective of this article is to highlight that modern topical ocular medical treatments, as well as laser and surgical procedures for glaucoma, are currently refocusing on working at the level of the conventional pathway (trabecular meshwork) since it is at that level where the increased resistance to the outflow of aqueous humor.